2010
DOI: 10.1002/cbdv.200900155
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Lipopeptide Methyl Esters Produced by Bacillus licheniformis HSN 221

Abstract: Lipopeptides and their analogues are of increasing interest due to their amphiphilic structures and potential applications in various fields. Three purified lipopeptides analogues were obtained at the same time after two-step column-chromatographic purification from cell-free broth cultivated by Bacillus licheniformis HSN 221. Analysis by ESI-MS, GC/MS, HPLC, and Q-TOF MS/MS revealed their primary structures as anteiso-C(15)- and iso-C(15)-beta-hydroxy fatty acid-Gln-Leu-Leu-Val-MeAsp-Leu-Ile, anteiso-C(15)- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…The amino acid sequences of surfactants produced by B. subtilis #309 were similar to those present in the surfactin standard (Figures S2-S6). These results indicate that the chemical structure of surfactants produced by B. subtilis #309 is very similar to that of other surfactin mixtures produced by different Bacillus strains [43][44][45].…”
Section: Evaluation Of Crude Glycerol From Different Sources As a Sub...supporting
confidence: 57%
“…The amino acid sequences of surfactants produced by B. subtilis #309 were similar to those present in the surfactin standard (Figures S2-S6). These results indicate that the chemical structure of surfactants produced by B. subtilis #309 is very similar to that of other surfactin mixtures produced by different Bacillus strains [43][44][45].…”
Section: Evaluation Of Crude Glycerol From Different Sources As a Sub...supporting
confidence: 57%
“…The loss of CH 3 OH ( m/z 1032.7 u) from the protonated molecule, found only jointly with the ion at m/z 699.5 u, confirms the presence of a methylated carboxyl group. The possibility of the extraction procedure causing methylation is excluded by its current use by many authors . This assignment is supported by the sequential loss of amino acid residues from the protonated molecule, starting from amino acid 7, as reported by other authors, and evidenced in the MS/MS spectra (Fig.…”
Section: Resultssupporting
confidence: 56%
“…However, in our case, the presence of Asp or m Asp in the amino acid sequence was ensured by the m/z value of the principal product ion, thus excluding an Asn in the peptide cycle. Literature data describe a similar structure as belonging to lichenysins (ions at m/z 1007.7–1063.7 u) …”
Section: Resultsmentioning
confidence: 86%
“…It was reported that the lactone ring could be opened by treatment with alkaline [ 10 , 11 ], the resulted linear surfactin lost 97% of the protoplast-bursting activity [ 10 ], had no significant hemolysis and the surface activity of it was reduced compared to the cyclic ones [ 12 ]. Considering about methylation, there are two possible approaches to get the methyl surfactin, chemical modification [ 2 , 4 , 13 , 14 , 15 , 16 , 17 ] and biosynthesis [ 18 , 19 , 20 ]. Because of the two carboxylic groups on side chains of the lactone ring, there would be different esterified derivatives.…”
Section: Introductionmentioning
confidence: 99%